Securing DICOM images by a new encryption algorithm using Arnold transform and Vigenère cipher - Boussif, Mohamed; Aloui, Noureddine; Cherif, Adnene (IET image processing, 2020)
This study presents a novel encryption method for the security of DICOM (Digital Imaging and Communications in Medicine) images used in medical applications. The proposed algorithm splits the original image into blocks of size 16 × 16 pixels, then encrypts it through three steps. Firstly, the keys k1, k2, k3 and k4 are transformed from four vectors of 16 pixels to a matrix of 16 × 16 pixels. Then, the proposed algorithm encrypts the image block-by-block using the Vigenère cipher algorithm. For each block, the proposed algorithm modifies the key using Arnold transform. The proposed encryption algorithm is scalable with colour images and JPEG (Joint Photographic Experts Group) compression. The cryptanalysis of the proposed algorithm demonstrates that it passed the cryptography attacks tests with success. Its running time shows that it is faster than a typical and recent image encryption algorithm.